High-throughput screening of TMOCl cathode materials based on the full-cell system for chloride-ion batteries. Issue 40 (8th October 2021) - Wu, Mengqi; Lv, Xiaohuan; Wang, Jianglong; Wang, Ruining; Shi, Xingqiang; Zhang, Hu; Jin, Chendong; Wei, Yingjin; Lian, Ruqian
Abstract : Discharge of the Li–CoOCl full-cell system and the Cl − migration path in CoOCl. Abstract : Transition metal oxychlorides (TMOCl) have attracted great attention as promising cathode materials for chloride ion batteries (CIBs). However, current research on TMOCl has been mainly focused on FeOCl and VOCl. On the other hand, the theoretical study of anionic rechargeable batteries faces the difficulty of predicting the discharge voltage of the electrode materials based on the half-cell system. Herein, a reliable theoretical voltage formula for CIBs is proposed based on a full-cell system with Li/LiCl as the reference anode. A high throughput screening method for TMOCl is applied among 16 transition metals. After the screening according to energetic and dynamic stability, Co is identified, which can form a new cathode material of CoOCl. Compared to FeOCl and VOCl, CoOCl has a higher discharge voltage, which is beneficial for achieving a larger energy density. The small crystal field splitting energy and exchange splitting energy of Co 3+ result in higher electronic conductivity. In addition, the uniform Cl − binding environment leads to a low Cl − diffusion barrier of 0.37 eV, which is much smaller than that of VOCl (0.65 eV) and FeOCl (0.58 eV).